2021
DOI: 10.3389/fpsyt.2021.738358
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cigarette Smoking With Male Cognitive Impairment and Metal Ions in Cerebrospinal Fluid

Abstract: Objective: Cigarette smoking might accelerate cognitive impairment; however, this has never been investigated using human cerebrospinal fluid (CSF). We conducted this study to investigate the association between cigarette smoking and cognitive impairment through metal ions in CSF.Methods: We obtained 5-ml CSF samples from routine lumbar puncture procedures in patients undergoing anterior cruciate ligament reconstruction before surgery in China. A total of 180 Chinese males were recruited (80 active smokers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 68 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…Most previous studies have shown a direct relationship between smoking and cognitive impairment and dementia (29), while in the present study, older adults who smoke had less cognitive impairment compared to non-smokers. Functional impairment was also lower in smokers than non-smokers.…”
Section: Characteristicscontrasting
confidence: 57%
“…Most previous studies have shown a direct relationship between smoking and cognitive impairment and dementia (29), while in the present study, older adults who smoke had less cognitive impairment compared to non-smokers. Functional impairment was also lower in smokers than non-smokers.…”
Section: Characteristicscontrasting
confidence: 57%
“…Especially in the aspect of early signs of diseases, among which disorders of the neurological system might be the first to appear 38 . Studies of Li et al 39 revealed that cigarette smoking might be associated with male cognitive impairment related to higher levels of iron (Fe), zinc (Zn), Pb, and Al in the human cerebrospinal fluid of active smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies by Durazzo et al and Pirpamer et al established that former smoking significantly increased the risk for AD from the damage caused by smoking-related cerebral oxidative stress, and identified this as a significant risk factor for cerebral iron accumulation, a habit that is also known to initiate endothelial dysfunction [ 47 , 48 ]. Another cross-sectional study by Li et al found significantly higher cerebrospinal fluid (CSF) iron concentration in active smokers than in non-smokers, suggesting that smoking may accelerate cognitive impairment [ 49 ]. The present study further propagates this knowledge by providing insight into how smoking alters the relationship between dietary iron intake and the incidence of dementia.…”
Section: Discussionmentioning
confidence: 99%